Prevalence and Weight Class Differences in Sleep Quality Among Competitive Jujitsu Athletes in Indonesia - Mohammad Krisno Bayu Seto; Dita Yuliastrid (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Sleep plays a critical role in physiological recovery, cognitive function, and optimal athletic performance. However, limited research has investigated sleep quality among combat sport athletes in Southeast Asia, particularly in weight-class sports such as Jujitsu. This study aimed to examine the prevalence and characteristics of sleep quality among competitive Jujitsu athletes in Surabaya, Indonesia. A descriptive quantitative cross-sectional design was employed involving 56 athletes selected using purposive sampling. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics and comparative analysis were used to examine sleep quality patterns across gender and weight categories. The results indicated that 69.6% of athletes experienced poor sleep quality, whereas 30.4% demonstrated good sleep quality. The overall mean PSQI score was 6.8 ± 2.6 (95% CI: 4.5–8.9), exceeding the established cutoff value (>5) and indicating generally poor sleep quality among the participants. Poor sleep quality appeared more prevalent among female athletes and those competing in lighter weight classes. Female athletes demonstrated slightly higher PSQI scores compared with male athletes, although the difference showed a small effect size (Cohen’s d ≈ 0.15) and was not statistically significant (p > .05). These findings highlight the need for structured sleep monitoring and targeted recovery strategies in combat sport training environments. Practical interventions such as sleep hygiene education, optimized training schedules, and monitoring of weight management practices may help improve sleep quality and support athletic performance among Jujitsu athletes.